Case Study on Community Based Sustainable Tourism Practices and Their Sustainability - Jain, Trilok Kumar (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 1 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2024)
Sustainable tourism stands as a pivotal objective for every city, with a plethora of distinct practices contributing to its advancement. This paper delves into the essence of sustainable tourism, aiming to shed light on practices fostering environmental preservation, community engagement, and cultural conservation. Despite the pervasive environmental degradation often associated with tourism, sustainable practices offer a pathway to mitigate such impacts and foster environmental harmony. Drawing upon the unique cultural ethos of the Bishnoi community in Western Rajasthan, exemplified by their unwavering commitment to tree conservation, this paper underscores the crucial interplay between cultural heritage and sustainable tourism. Through an exploration of the historical evolution of sustainable tourism in Bikaner, this study elucidates how traditional customs, such as pilgrimage on foot and community-led festivals, intertwine with sustainable tourism practices, fostering pollution reduction and cultural preservation. Furthermore, an analysis of the impact of tourism in Bikaner reveals the pivotal role of community involvement in ensuring the sustainability and inclusivity of tourism initiatives. However, amidst the strides made by local communities, the absence of robust governmental support poses a challenge to the preservation and revitalization of these sustainable practices. Thus, this paper advocates for the recognition and amplification of indigenous sustainable tourism practices, underscoring the imperative for collaborative efforts between local communities and governmental authorities to realize a truly model city of sustainable tourism.